2007
DOI: 10.1097/mbc.0b013e328010bcde
|View full text |Cite
|
Sign up to set email alerts
|

Severe prekallikrein deficiencies due to homozygous C529Y mutations

Abstract: Two consecutive severe prekallikrein deficiencies were investigated. The first was identified in a 63-year-old patient admitted for ischemic stroke. The second deficiency was identified in a 38-year-old patient admitted for a second-trimester pregnancy loss. A homozygous C529Y mutation was identified for both cases, whereas they are unrelated and no consanguineous marriage is known from the patients. These data point to a possible high frequency of this mutation as a cause of prekallikrein deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Twenty-one out of the 89 patients had hypertension or hypertension-related conditions [6,8,12,14,15,[17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Twelve were men and nine women (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one out of the 89 patients had hypertension or hypertension-related conditions [6,8,12,14,15,[17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Twelve were men and nine women (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…They belonged to 56 separate kindreds [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47]. A thrombotic event was reported in 9 of these patients belonging to 6 different families (table 1) [5,16,22,23,24,28]. …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the mutant form does not have Cys-529, which is known to play an important role in prekallikrein function. It is reported that a homozygous C529Y mutation results in severe prekallikrein deficiency [13]. Therefore, it is highly probable that the mutation leads to severe prekallikrein deficiency, although inheritance analysis for this mutation was not performed.…”
Section: Discussionmentioning
confidence: 98%